The Impact of Urbanization on Surface Runoff and Flood Prevention Strategies: A Case Study of a Traditional Village - Jiaxin Li; Wuzhong Zhou; Cong Tao (Land)
Increasingly severe flooding disasters have caused heavy casualties and property losses worldwide. Traditional Chinese villages that rarely experienced flooding disasters in the past have begun to frequently suffer from floods due to unreasonable reconstruction activities such as ground hardening and pond filling caused by urbanization. However, previous studies on hydrological changes and flood disasters caused by reconstruction activities in rural areas are scarce, especially lacking in quantitative analysis and research. In this study, the Storm Water Management Model (SWMM) is used to construct two hydrological models before and after the reconstruction of Hezhai Village, a traditional Chinese village. By simulating and comparing the changes in hydrological indicators of the two models, this study quantitatively analyzes how reconstruction activities caused changes in surface runoff and flooding disasters in Hezhai Village. The results show that the increase in the impervious ratio in the village has obvious effects on the total runoff, peak runoff, and runoff coefficient. And the reconstruction of ponds and canals has a notable impact on flooding. This study further delves into the logic of flooding at ponds and ordinary nodes and analyzes the specific reasons for flooding in Hezhai Village. Based on this, the paper provides recommendations for the optimization of the reconstruction of Hezhai Village.